SHI/STY Genes Affect Pre- and Post-meiotic Anther Processes in Auxin Sensing Domains in Arabidopsis - Estornell, Leandro H.; Landberg, Katarina; Cierlik, Izabela; Sundberg, Eva (Frontiers in Plant Science, 2018)
In flowering plants, mature sperm cells are enclosed in pollen grains formed in structures called anthers. Several cell layers surrounding the central sporogenous cells of the anther are essential for directing the developmental processes that lead to meiosis, pollen formation, and the subsequent pollen release. The specification and function of these tissues are regulated by a large number of genetic factors. Additionally, the plant hormone auxin has previously been shown to play important roles in the later phases of anther development. Using the R2D2 auxin sensor system we here show that auxin is sensed also in the early phases of anther cell layer development, suggesting that spatiotemporal regulation of auxin levels is important for early anther morphogenesis. Members of the SHI/STY transcription factor family acting as direct regulators of YUC auxin biosynthesis genes have previously been demonstrated to affect early anther patterning. Using reporter constructs we show that SHI/STY genes are dynamically active throughout anther development and their expression overlaps with those of three additional downstream targets, PAO5, EOD3 and PGL1. Characterization of anthers carrying mutations in five SHI/STY genes clearly suggests that SHI/STY transcription factors affect anther organ identity. In addition, their activity is important to repress periclinal cell divisions as well as premature entrance into programmed cell death and cell wall lignification, which directly influences the timing of anther dehiscence and the pollen viability. The SHI/STY proteins also prevent premature pollen germination suggesting that they may play a role in the induction or maintenance of pollen dormancy.